2019
DOI: 10.1177/0886260519888196
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Intimate Partner Violence Among Married Women in Egypt

Abstract: Intimate partner violence (IPV) among married women of childbearing age can significantly enhance their risk of adverse health outcomes such as injury and disability, depression and anxiety, unwanted pregnancies, premature labor, complications with delivery, and perinatal and neonatal mortality. The objective of this study was to examine the prevalence and individual and societal factors associated with IPV among Egyptian women. Cross-sectional data on 12,205 ever-married women between the ages of 15 to 49 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
7
24
1
1
Order By: Relevance
“…the present study is higher compared to that reported in other studies such as Egypt with IPV prevalence was 29.4% with 26.7% physical, 17.8% psychological and 4.6% sexual violence(18), Nepal overall IPV psychological, physical and sexual violence was 18.3 %, 15.2 % and 2.3 % respectively among married women…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…the present study is higher compared to that reported in other studies such as Egypt with IPV prevalence was 29.4% with 26.7% physical, 17.8% psychological and 4.6% sexual violence(18), Nepal overall IPV psychological, physical and sexual violence was 18.3 %, 15.2 % and 2.3 % respectively among married women…”
contrasting
confidence: 78%
“…These variation of ndings observed in the prevalence of IPV, could be contributed by many factors, for example having outside sexual partners, alcohol use, early marriage, cohabiting, attitudes of supportive wife beating, experiencing childhood abuse, growing up with domestic violence and experiencing forms of violence in adulthood were mentioned to increase the risk of IPV practice (21). (18).…”
Section: Discussionmentioning
confidence: 99%
“…The covariates included in our study were selected based on their significant associations with IPV [ 25 , 26 , 27 , 28 ] and also their availability in the DHS dataset. The covariates include maternal age, marital status, wealth, maternal education level, place of residence, and mass-media exposure.…”
Section: Methodsmentioning
confidence: 99%
“…In SSA, where IPV has been found to be predominant, several scholars have made efforts to understand the predictors of IPV, with some identifying socio-demographic factors such as age at first marriage, spousal age difference, education, wealth index, place of residence, among other factors as predictors ( Ahinkorah et al, 2018 ; Akamike, Uneke, Uro-Chukwu, Okedo-Alex, & Chukwu, 2019 ; Dim, 2020 ; Izugbara, Obiyan, Degfie, & Bhatti, 2020 ; McCloskey, Boonzaier, Steinbrenner, & Hunter, 2016 ; Yaya, Hudani, Buh, & Bishwajit, 2019 ). Other studies have established an association between women's autonomy or household decision-making capacity and IPV ( Ahinkorah et al, 2018 ; Tenkorang, 2018 ; Zegenhagen, Ranganathan, & Buller, 2019 ).…”
Section: Introductionmentioning
confidence: 99%